Impact of quality of life on overall work productivity impairment and activity impairment of patients with systemic lupus erythematosus: the PEONY study - Yoshiya Tanaka; Shintaro Hirata; Shingo Nakayamada; Yusuke Miyazaki; Kazuyoshi Saito; Kunihiro Yamaoka; Shigeru Iwata; Yoshiyuki Yamaguchi; Keisuke Nakatsuka; Shunpei Kosaka; Katsuhide Kusaka; Toshiki Yabe-Wada; et al. (Lupus Science and Medicine)
Objectives Even in a lupus low disease activity state (LLDAS), many patients with SLE continue to face residual symptoms and disease burden. We aimed to evaluate the quality of life, activity impairment and overall work productivity impairment among patients in LLDAS. Residual disease burden was also evaluated for patients in LLDAS.Methods This prospective, cross-sectional study enrolled Japanese outpatients with SLE. Patients completed patient-reported outcome (PRO) questionnaires, including LupusPRO, Work Productivity and Activity Impairment-Lupus, EQ-5D-5L and Health Assessment Questionnaire-Disability Index. Disease activity and organ damage were investigator-assessed. The primary objective was to assess the residual burden in patients in LLDAS and to investigate the association of LupusPRO domains with activity impairment using multivariate regression analysis. Other objectives were to investigate the relationship between overall work productivity impairment or activity impairment and other PRO or disease activity measures.Results The analysis set included 205 patients; 93.2% were female, mean (SD) age at index date was 52.5 (14.7) years, mean (SD) duration of morbidity was 167.2 (125.2) months and 164 were in LLDAS. The mean per cent overall work productivity impairment was 22.8% and mean per cent activity impairment was 30.0% for the LLDAS group. Among patients in LLDAS, overall work productivity impairment was significantly associated with the LupusPRO domains Desires-Goals, Body Image and Pain Vitality, and activity impairment was significantly associated with the LupusPRO domains Pain Vitality, Physical Health and Lupus Symptoms.Conclusions Patients with SLE in LLDAS still experience symptoms associated with activity impairment. Work productivity also showed impairments. Improving their quality of life and achieving social remission will require ongoing monitoring of PROs and tailoring treatments to optimise these outcomes.Trial registration number jRCT1030210647.